Mutational screening of six afibrinogenemic patients: Identification and characterization of four novel molecular defects - Monaldini, Luca; Asselta, Rosanna; Duga, Stefano; Peyvandi, Flora; Karimi, Mehran; Malcovati, Massimo; Tenchini, Maria Luisa (Thrombosis and Haemostasis, 2007)
Congenital afibrinogenemia (CAF) is a rare coagulation disorder characterized by very low or unmeasurable levels of functional and immunoreactive fibrinogen in plasma, associated with a hemorrhagic phenotype of variable severity. It is transmitted as an autosomal recessive trait (prevalence 1:1,000,000) and is invariantly associated with mutations affecting one of the three fibrinogen genes (FGA, FGB, and FGG, coding for Aα, Bβ, and γ chain, respectively). Fibrinogen is secreted by hepatocytes as a hexamer composed of two copies of each chain; the lack of one chain has been demonstrated to prevent its secretion. Most genetic defects causing afibrinogenemia are point mutations, where- as only three large deletions have been identified so far, all affecting the FGA gene. We here report the molecular characterization of six unrelated afibrinogenemic patients leading to the identification of eight different mutations, four hitherto unknown: a 4.1-Kb large deletion involving exon 1 of FGA (AC107385:g. 65682_69828del), two nonsense mutations (p.Trp229X in FGA and p.Trp266X in FGB), and an ins-del mutation (g.1787_ 1789del3ins12) in FGA. The molecular characterization of CAFcausing genetic defects increases our understanding on the genetic basis of this disease and might be helpful for prenatal screening purposes, as also demonstrated during this study.
Keywords: Fibrinogen; congenital afibrinogenemia; mutational screening; large deletion; point mutations